Problems and challenges in modelling and forecasting Caribbean economies - Nicholls, Shelton Michael Anthony ed. (Caribbean Centre for Monetary Studies St. AugustineTT, 1996)
Provides an account of the history of and problems with macroeconometric modelling in the Caribbean. Explores the use of various modelling strategies to assess important developments in the monetary and financial sector of Caribbean Basin countries. Provides suggestions on alternative modelling designs and articulates a framework for improving the organisation and analysis of data.